The potential use of genomic methods in bottom trawl surveys to improve stock assessments in Europe - Rodríguez-Mendoza, Rebeca; Saborido-Rey, Fran (Frontiers in Marine Science, 2023)
In Europe, the vast majority of fishery-independent data comes from research surveys conducted by state governments. Member States (MS) in the European Union (EU) regularly conduct research surveys of marine fishery resources to provide fundamental data for assessing the condition of exploited fish stocks and for monitoring the general status of the marine ecosystem. In the surveys, samples are taken throughout the potential range of the targeted fish species using standardized sampling gears including trawls and seines, hydroacoustics and video. In the context of fish stock assessment, survey data are important because they provide indices that help tuning the stock assessment models (e.g., the index of fish abundance) and key information on the size and age distributions of the stock, the size-age relationships, estimates of the percentage of fish mature at each age, and information on reproductive performance of the stocks. However, research surveys have a number of shortcomings that include, for example, a high economic cost coupled with complex logistics and a long time required for treating and analyzing the collected data. In addition, some of the parameters that are needed in stock assessment cannot be estimated from survey data for certain commercially important species. For instance, age is usually determined using hard structures (such as otoliths) in fish target species. However, for European hake, age cannot be determined accurately because there are many difficulties in interpreting the ring patterns of the otoliths. This highlights the need to look for alternative methodologies such as genomics, that have the potential of improving the data obtained from research surveys and hence, improve fish stock assessments. Considering this, we carried out a review of the bottom trawl research surveys in the EU with the purpose of: 1) identifying the current approaches for monitoring fishery resources and the ecosystem and 2) determining how genomic techniques can be used to improve survey data, taking into account the needs of current and future stock assessment in Europe.